Anca-associated crescentic glomerulonephritis in a child with isolated renal involvement - Çelakıl,Mehtap Ezel (2019)
ABSTRACT Pauci-immune glomerulonephritis (GN) is more common in elderly people compared to children and the etiology is not completely understood yet. Antineutrophil cytoplasmic antibody (ANCA) positivity occurs in 80% of the patients. We report a case of a 7-year-old girl who presented with malaise and mildly elevated creatinine diagnosed as ANCA-associated pauci-immune crescentic glomerulonephritis with crescents in 20 of 25 glomeruli (80%). Of these 20 crescents, 12 were cellular, 4 fibrocellular, and 4 globally sclerotic. She did not have purpura, arthritis, or systemic symptoms and she responded well to initial immunosuppressive treatment despite relatively severe histopathology. The patient was given three pulses of intravenous methylprednisolone (30 mg/kg on alternate days) initially and continued with cyclophosphamide (CYC; 2 mg/kg per day) orally for 3 months with prednisone (1 mg/kg per day). In one month, remission was achieved with normal serum creatinine and prednisone was gradually tapered. The case of this child with a relatively rare pediatric disease emphasizes the importance of early and aggressive immunosuppressive treatment in patients with renal-limited ANCA-associated pauci-immune crescentic GN even if with a mild clinical presentation. As in our patient, clinical and laboratory findings might not always exactly reflect the severity of renal histopathology and thus kidney biopsy is mandatory in such children to guide the clinical management and predict prognosis.